Humanization of the relationship between young and older generations - Rusina E. I. (Social-Psychological Issues of a Contemporary Family: Value of Motherhood and Childhood, 2021)
In modern society, especially among young people, negative stereotypes of attitudes towards old age are often manifested, which negatively affect not only the elderly and elderly people themselves, but also the culture of society as a whole, the development of civilized intergenerational relations, social ties. The current situation poses both socio-economic, socio-pedagogical, psychological and moral problems for Russian society, primarily related to the search for ways to activate older people in various spheres of life, humanization of the relationship between young and older generations, the full use of the life, social and professional experience of older people and their protection, socio-pedagogical support.
Keywords: педагогика; воспитание; семья; family; поколение; pedagogy; upbringing; generation; intergenerational relations; межпоколенческие отношения